2012
DOI: 10.1007/s00330-012-2541-z
|View full text |Cite
|
Sign up to set email alerts
|

Can radiographers be trained to triage CT colonography for extracolonic findings?

Abstract: ObjectivesRadiographers have been shown to be capable CT colonography observers. We evaluated whether radiographers can be trained to triage screening CT colonography for extracolonic findings.MethodsEight radiographers participated in a structured training program. They subsequently evaluated extracolonic findings in 280 low-dose CT colonograms (cases). This dataset contained 66 cases with possibly important findings (E3) and 27 cases with probably important findings (E4) [classification based on the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…It is well known that radiological readers with more experience will have better diagnostic performance. Moreover, in different imaging settings (for example, reading of mammograms, CT colonography examinations and MRI for diagnosing endometriosis) it has been demonstrated that a learning curve is required before non-expert readers can reach a certain diagnostic performance level [10][11][12]. Teaching is therefore an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that radiological readers with more experience will have better diagnostic performance. Moreover, in different imaging settings (for example, reading of mammograms, CT colonography examinations and MRI for diagnosing endometriosis) it has been demonstrated that a learning curve is required before non-expert readers can reach a certain diagnostic performance level [10][11][12]. Teaching is therefore an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, a Dutch study in 2012 invited eight radiographers to engage in a structured training programme, to triage cases based on the CT colonography reporting and data system and to flag the appropriate scans for a radiologist review. They found that correct identification of E3 findings improved from 52 to 70% after training, but identification of E4 findings was unchanged at 69% [ 18 ]. As such, radiographers should not be expected to identify all extracolonic findings.…”
Section: Discussionmentioning
confidence: 99%